How are Public Libraries in Alberta Responding to the Needs of Older Adults? A Literature Review - Kirman, Paula (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
Despite the increasing number of adults aged 60 and older, there is a gap in studies of library programming and services aimed at this demographic in Canada, especially ones based in the western part of the country. This literature review will examine existing studies in the area of public library programming for older adults, as well as how these libraries are meeting the needs of older patrons in terms of issues pertaining to accessibility and accommodations.